Wissenschaftliche Verfassungsrechtspolitik? - Bryde, Brun-Otto (Mohr Siebeck, 2023)
Can constitutional politics be conducted in a scholarly manner? For some, the question does not arise, because constitutional dogmatics always inevitably works in a legal-political way. For others, dogmatics is characterised precisely as the counterpart to politics; accordingly, constitutional policy pursued in a scholarly manner is a contradictio in adiecto.
PublicationDate: 20230930
Keywords: Amt und Person -- Verfassungsdogmatik -- Hans F. Zacher -- Wissenschaft und Politik -- Wissenschaftliche Wissensproduktion -- Verantwortung der Rechtswissenschaft -- Kurzfristdenken -- Rechtstheorie -- Verfassungsrecht und Staatslehre